2016
DOI: 10.18632/oncotarget.8154
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma cancer stem cells

Abstract: Multiple myeloma (MM) remains incurable despite much progress that has been made in the treatment of the disease. MM cancer stem cell (MMSC), a rare subpopulation of MM cells with the capacity for self-renewal and drug resistance, is considered to lead to disease relapse. Several markers such as side population (SP) and ALDH1+ have been used to identify MMSCs. However, ideally and more precisely, the identification of the MMSCs should rely on MMSCs phenotype. Unfortunately the MMSC phenotype has not been prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 98 publications
0
44
0
Order By: Relevance
“…Another possibility is that BCNU could have effects on the bone marrow microenvironment, thus rendering MM cells more susceptible to chemotherapy. 31,32 Our finding that 21% of patients treated with BCNU/HDM remained without evidence of progressive disease over 10 years post transplant in the absence of any additional maintenance therapy suggests that a distinct effect is occurring with this combination, as this number is measurably higher than that experienced with HDM alone. 1,27,28 The growing evidence of clonal heterogeneity and evolution throughout the myeloma disease course has been supported by genomic studies showing that patient myeloma cell populations experience both linearly derived and branching clonal evolution.…”
Section: Discussionmentioning
confidence: 93%
“…Another possibility is that BCNU could have effects on the bone marrow microenvironment, thus rendering MM cells more susceptible to chemotherapy. 31,32 Our finding that 21% of patients treated with BCNU/HDM remained without evidence of progressive disease over 10 years post transplant in the absence of any additional maintenance therapy suggests that a distinct effect is occurring with this combination, as this number is measurably higher than that experienced with HDM alone. 1,27,28 The growing evidence of clonal heterogeneity and evolution throughout the myeloma disease course has been supported by genomic studies showing that patient myeloma cell populations experience both linearly derived and branching clonal evolution.…”
Section: Discussionmentioning
confidence: 93%
“…A growing body of evidence suggests that a minor, therapy-resistant, clonogenic sub-population of tumor cells is most likely the principal roadblock to curing MM [4, 8]. However, the identity of these stem-like MM cells remains only partially resolved [5, 7].…”
Section: Discussionmentioning
confidence: 99%
“…OCT4, NANOG, SOX2), drug resistance and chromosomal instability genes (i.e. NEK2, BTK, RARĪ±2), BCRP , and/or ALDH1A1 expression has been used to identify stem-like MM cells [7, 8]. In the present study we have used two established markers of MM stem-like cells (CD138 immunophenotyping and SP staining) to characterize the oxidative metabolic properties of stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those drugs were able to inhibit CD138+ PCs growth [234][235][236]. Nonetheless, another study demonstrated that clonotypic CD138 + PCs also have some properties of CSCs such as self-renewal, tumour-initiating potential and drug resistance [237,238]. A more recent study with gene expression profiling of putative CSCs and the main population of MM cells derived from 11 MM patients, identified CD24+ MM cells as being capable of maintaining CSC features of self-renewal and drug resistance [239].…”
Section: Persistence Of Cancer Stem Cellsmentioning
confidence: 99%